2013
DOI: 10.3109/02770903.2013.834506
|View full text |Cite
|
Sign up to set email alerts
|

Acid–base patterns in acute severe asthma

Abstract: Predominant acid-base patterns observed in ASA in this patient population included primary hypocapnia, or less frequently, primary hypercapnia. Lactic acidosis occurred in 11% of patients and presented consistently as a mixed acid-base disorder. These findings suggest lactic acidosis results from the combined effects of both ASA and medication-related sympathetic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
4
1
1
Order By: Relevance
“…While blood gas disturbances have been demonstrated in patients with an acute asthma exacerbation, with respiratory alkalosis present predominantly in patients with mild airway obstruction (29), few studies evaluated its presence in a stable state of disease, that is, outside the remits of an acute exacerbation (16). The prevalence of hypocapnia in 40% of the patients with asthma in a stable state of disease in the current study is higher compared to the few earlier studies addressing this issue.…”
Section: Discussioncontrasting
confidence: 57%
“…While blood gas disturbances have been demonstrated in patients with an acute asthma exacerbation, with respiratory alkalosis present predominantly in patients with mild airway obstruction (29), few studies evaluated its presence in a stable state of disease, that is, outside the remits of an acute exacerbation (16). The prevalence of hypocapnia in 40% of the patients with asthma in a stable state of disease in the current study is higher compared to the few earlier studies addressing this issue.…”
Section: Discussioncontrasting
confidence: 57%
“…LA concentrations vary widely with metabolic activity and tissue perfusion, and correlate with clinical features. For example, LA or lactate levels are linked to outcomes or severity in cancer [22][23][24][25], sepsis [26], pulmonary embolism [27], and asthma [2,28,29]. But more than just a marker of glucose metabolism, LA is functionally important.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the absence of pulsus paradoxus makes the presence of hypercapnia unlikely, although it is noted that clinical signs and symptoms during acute severe asthma often are not correlated with the severity of the functional impairment [19]. Raimondi et al performed a case series study exploring acid-base patterns in patients admitted for acute severe asthma, in correlation with forced expiratory volume in 1 s (FEV 1 ) values [8]. Airway obstruction severity did not seem to correlate significantly with PaO 2 values, a finding also reported in several other studies in the past [18,20,21] and thought to be due to V A /Q mismatch not being connected to air flow rates; moreover, treatment with β-agonists may lead to further widening of V A /Q mismatch.…”
Section: Respiratory Acidosismentioning
confidence: 99%